COBITIS-ELAZIGENSIS, A NEW SPECIES OF COBITIDID FISH FROM ANATOLIA, TURKEY - COAD, BW; SARIEYYUPOGLU, M (Ichthyological Soc Japan, 1988)
A new cobitidid, Cobitis elazigensis, is described from Anatolian Turkey in the province of Elazig. The new species differs from all other members of the genus by having the following combination of characters: two Canestrini''s scales on the pectoral fin, a suborbital spine with a dorso-lateral branch (rarely simple and unbranched), large size, over 180 mm total length, total vertebrae 47-49, lateral spots reduced or absent, a spot at the upper caudal fin base, scales longer than wide with a small focus, dorsal fin rays III, 5-6, usually 6, ventral fin rays III, 6-7, usually 6, and pectoral fin rays I, 7-9.